Compositional dependence of electrical conduction in solution grown Zn1-xCrxSe thin films: a correlation - Deshmukh, S. L.; Pingale, P. C.; Chavan, G. T.; Pawar, S. T.; Prakshale, V. M.; Kamble, S. S.; Jadkar, S. R.; Chaure, N. B.; Gopinath, C. S.; Maldar, N. N.; Deshmukh, L. P. (Journal of Materials Science: Materials in Electronics, 2017)
Zinc selenide (ZnSe) has a typical band gap of 2.7 eV suitable for window application and can easily be synthesized using a liquid phase chemical bath deposition. An attempt is made to tune its band gap and other characteristics to cope with a maxima of the solar spectrum by deliberate addition of Cr3+. ZnSe and Zn1-xCrxSe (0 <= x <= 0.35) thin films were obtained under the controlled deposition conditions (temperature = 70 A degrees C, time = 210 min, pH = 10, etc). The compositional analysis showed Zn2+ replacement by Cr3+. The X-ray photoelectron spectroscopy revealed chemical states of the constituents Zn, Cr and Se as 2(+), 3(+) and 2(-) respectively. The electrical conductivity and thermo-power measurements in the 300-550 K temperature range showed semiconducting nature of the material and that the electrical conduction is of the n-type. The electrical conductivity is found to be increased continuously up to x = 0.05 and then decreased for further increase in x. The Hall-probe measurements also confirmed n-type conduction. The average Hall coefficient for pure ZnSe is -1.03 x 10(7) cm(3)/C whereas, it is -4.55 x 10(6) cm(3)/C for a sample with x = 0.35.

Study of photoelectrochemical conductivity mechanism and electrochemical impedance spectroscopy of bulk CuInTe2 – Electrolyte interface - Lakhe, M. G.; Rohom, A. B.; Londhe, P. U.; Bhand, G. R.; Chaure, N. B. (Surfaces and interfaces, 2018)
CuInTe2 (CIT) thin films were electrochemically deposited in an aqueous electrolyte on fluorine doped tin oxide (FTO) coated glass substrates for potentials ranging from −0.6 V to −0.9 V at pH 4. Films were annealed at 400 °C for 15 min in air ambient. Both as-deposited and annealed layers were characterized by various characterization techniques. The conductivity type of the CIT layers was studied by photoelectrochemical (PEC) response and solid–electrolyte interface by impedance spectroscopy. As-deposited samples confirmed amorphous nature of CIT in contrast to that of polycrystalline films obtained upon annealing. Three prominent reflections (1 1 2), (2 2 0)/(2 0 4) and (3 1 2)/(1 1 6) of chalcopyrite CIT were obtained upon annealing. The optical band gap values ∼0.90 eV and 1.08 eV and ∼0.88 eV and 1.01 eV were estimated for as-deposited and annealed CIT layers deposited at −0.7 V and −0.8 V respectively. The most prominent A1 mode observed at 123 cm−1 in the Raman spectra of chalcopyrite CIT was shifted towards lower wavelengths due to the development of tensile strain. Very compact, well adhesive and void free globular layers were deposited at pH 4. The indium content was found to be increased with increasing the deposition potential which agrees well with the overpotential deposition of indium. Photoelectrochemical (PEC) study confirms the growth of p-type CIT layers. The negative resistance at higher frequency domain (3 MHz to 10 kHz) from electrochemical impedance spectroscopy (EIS) confirms the power/energy giving nature of CIT/electrolyte interface at higher frequency and diffusion mechanism of ionic species dominate at lower frequency region